Implementasi Metode Drill and Practice dalam Komunikasi Berbahasa Jawa di Media Sosial - Prima Veronika; Budi Waluyo; Kenfitria Diah Wijayanti; Tya Resta Fitriana; Djoko Sulaksono; Astiana Ajeng Rahadini; Winda Dwi Lestari; Rahmat Rahmat; Favorita Kurwidaria; Dewi Pangestu Said (Universitas Sebelas Maret, 2024)
The aim of this research is to explain the implementation of the drill and practice method to train students' communication in Javanese on social media. The method used is drill and practice. The results of the service show that there are students who do not dare to use Javanese appropriately when communicating in the real world and the virtual world. Some students feel hesitant when asking or answering using Javanese. The service team then interacted with the students to practice using the drill and practice method. Students are invited to interact in groups by practicing orally and in writing using simple Javanese words. Through the drill and practice method, they are able to practice Javanese conversation and writing according to uploads well and correctly based on the person they are communicating with. Students are able to write Javanese sentences in the form of congratulations, greetings, condolences, thank you which are often used on their social media.